Coding Variants Coupled With Rapid Modeling in Zebrafish Implicate Dynein Genes, dnaaf1 and zmynd10, as Adolescent Idiopathic Scoliosis Candidate Genes - Wang, Yunjia; Liu, Zhenhao; Yang, Guanteng; Gao, Qile; Xiao, Lige; Li, Jiong; Guo, Chaofeng; Troutwine, Benjamin R.; Gray, Ryan S.; Xie, Lu; Zhang, Hongqi (Frontiers in Cell and Developmental Biology, 2020)
Adolescent idiopathic scoliosis (AIS) is the most common pediatric spine disorder, affecting 3% of children worldwide. Human genetic studies suggest complex polygenic disease model for AIS with large genetic and phenotypic heterogeneity. However, the overall genetic etiology of AIS remains poorly understood. To identify additional AIS susceptibility loci, we performed whole exome sequencing (WES) on a cohort of 195 southern Chinese AIS patients. Bioinformatics analysis identified 237 novel rare variants associated with AIS, located in 232 new susceptibility loci. Enrichment analysis of these variants revealed 10 gene families associated with our AIS cohort. We screened these gene families by comparing our candidate gene list with IS candidate genes in the Human Phenotype Ontology (HPO) database and previous reported studies. Two candidate gene families, axonemal dynein and axonemal dynein assembly factors, were retained for their associations with ciliary architecture and function. The damaging effects of candidate variants in dynein genes dnali1, dnah1, dnaaf1, zmynd10, as well as in one fibrillin related gene tns1 were functionally analyzed in zebrafish using targeted CRISPR/Cas9 screening. Knockout of two candidate genes, dnaaf1 or zmynd10, recapitulated scoliosis in viable adult zebrafish. Altogther, our results suggest that the disruption of one or more dynein associated factors may correlate with AIS susceptibility in southern Chinese population.